Function resulting from the form – adapting the post-war modernist architecture for new functional programs - Ciarkowski, Błażej (Protection of Cultural Heritage, 2020)
The aim of this article is to analyze the possibilities of adaptation of modernist architecture objects erected in Poland after World War II. The specificity of the form, which was designed in the spirit of functionalism, and thus adapted to a specific functional program, makes it much more difficult to change the purpose of the objects. Similarly, material and structural solutions, which (sometimes due to their experimental, innovative character) poorly stand the test of time. Considerations on introducing new functional programs while maintaining the authenticity of objects have been illustrated with selected examples of implementation, which are to prove the thesis that the final effect of the adaptation process depends, among others, on the proper interpretation of the historical substance and the idea behind its origin.